Fruit regulates seasonal expression of flowering genes in alternate-bearing ‘Moncada’ mandarin - Muñoz-Fambuena, Natalia (Oxford University Press, 2011)
BACKGROUND AND AIMS: The presence of fruit has been widely reported to act as an inhibitor of flowering in fruit trees. This study is an investigation into the effect of fruit load on flowering of ‘Moncada’ mandarin and on the expression of putative orthologues of genes involved in flowering pathways to provide insight into the molecular mechanisms underlying alternate bearing in citrus. METHODS: The relationship between fruit load and flowering intensity was examined first. Defruiting experiments were further conducted to demonstrate the causal effect of fruit removal upon flowering. Finally, the activity of flowering-related genes was investigated to determine the extent to which their seasonal expression is affected by fruit yield. KEY RESULTS: First observations and defruiting experiments indicated a significant inverse relationship between preceding fruit load and flowering intensity. Moreover, data indicated that when fruit remained on the tree from November onwards, a dramatic inhibition of flowering occurred the following spring. The study of the expression pattern of flowering-genes of on (fully loaded) and off (without fruits) trees revealed that homologues of FLOWERING LOCUS T (FT), SUPRESSOR OF OVEREXPRESSION OF CONSTANS 1 (SOC1), APETALA1 (AP1) and LEAFY (LFY) were negatively affected by fruit load. Thus, CiFT expression showed a progressive increase in leaves from off trees through the study period, the highest differences found from December onwards (10-fold). Whereas differences in the relative expression of SOC1 only reached significance from September to mid-December, CsAP1 expression was constantly higher in those trees through the whole study period. Significant variations in CsLFY expression only were found in late February (close to 20 %). On the other hand, the expression of the homologues of TERMINAL FLOWER 1 (TFL1) and FLOWERING LOCUS C (FLC) did not appear to be related to fruit load. CONCLUSIONS: These results suggest for the first time that fruit inhibits flowering by repressing CiFT and SOC1 expression in leaves of alternate-bearing citrus. Fruit also reduces CsAP1 expression in leaves, and the significant increase in leaf CsLFY expression from off trees in late February was associated with the onset of floral differentiation.